Bis(amido) rare-earth complexes coordinated by tridentate amidinate ligand: synthesis, structure and catalytic activity in the polymerization of isoprene and rac-lactide. Issue 22 (11th February 2016) - Tolpygin, Aleksei O.; Linnikova, Olesya A.; Glukhova, Tatyana A.; Cherkasov, Anton V.; Fukin, Georgy K.; Trifonov, Alexander A.
Abstract : Rare-earth bis(amides) {2-[Ph2 Р(O)]C6 H4 NC( t Bu)N(2, 6-Me2 C6 H3 )}Ln(N(SiMe3 )2 )2 (Ln = Y, Nd, La) coordinated by tridentate amidinate ligand were synthesized, structurally characterized and evaluated as catalysts for isoprene and rac -lactide polymerizations. Abstract : A series of bis(amido) complexes of rare earth metals {2-[Ph2 P(O)]C6 H4 NC( t Bu)N(2, 6-Me2 C6 H3 )}Ln(N(SiMe3 )2 )2, (Ln = Y (2 ), Nd (3 ), La (4 )) was synthesized using the amine elimination reaction of Ln[N(SiMe3 )2 ]3 (Ln = Y, Nd, La) and parent amidine1 in THF, and the products were isolated in 60 (2 ), 61 (3 ) and 72% (4 ) yields, respectively. The X-ray studies revealed that complexes2–4 are solvent-free and feature intramolecular coordination of the Ph2 PO group to the Ln ion. Complexes2–4 were investigated as precatalysts for isoprene polymerization. The ternary systems2–4 /borate/AlR3 (AlR3 = AliBu3, AliBu2 H; borate = [Ph3 C][B(C6 F5 )4 ], [PhNHMe2 ][B(C6 F5 )4 ]) were found to be active in isoprene polymerization and enable complete conversion of 1000 equivalents of monomer into polymer at 25 °C within 1–24 h affording polyisoprenes with polydispersities M w / M n = 1.12–9.46. The effect of the organoaluminium component and [Ln]/[AlR3 ] ratio on the catalytic activity and selectivity of the ternary catalytic systems was investigated. Complexes2–4 proved to be efficient catalysts for the ring-opening polymerization of rac -lactide, which allow conversion of up to 500 equivalents of monomer into a polymer at room temperature within 30 min and afford atactic polylactides with high molecular weights and moderate molecular-weight distributions (1.29–2.12). Complexes2–4 appear to be well-suited for achieving immortal polymerization of lactide, through the introduction of large amounts of isopropanol as a chain-transfer agent.